Disaster Prone Areas and Stunting Prevalence in Indonesia: Ecological Study of 34 Provinces - Lestari, Endah Febri; Sudaryo, Mondastri Korib (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2023)
Indonesia has a high intensity of disaster events. The prevalence of under-five stunting in Indonesia is also high. One of the targets of the Ministry of Health's Medium-Term Development Plan for 2020-2024 is to reduce stunting in children by 14% in 2024. This study aims to look at the relationship between disaster risk and the prevalence of stunting in 34 provinces in Indonesia. The study design is an ecological study approach sourced from the 2021 Indonesian Disaster Risk Index (IRBI), the 2021 Indonesian Nutritional Status Survey (SSGI), the 2018 Basic Health Research and the 2021 National Socioeconomic Survey (Susenas). This study conducted a spatial analysis, scatter plots, pearson correlation test and multivariable linear regression. From the results, it found that the higher risk of disaster increased the tendency for the prevalence of under-five stunting. It was concluded that disaster risk has a positive relationship with the prevalence of under-five stunting in Indonesia. We suggest that a disaster management program can be considered to reduce stunting in Indonesia.